Engineering bacteria for diagnostic and therapeutic applications - Riglar,DT; Silver,PA (Nature Reviews Microbiology, 2018)
Our ability to generate bacterial strains with unique and increasingly complex functions has rapidly expanded in recent times. The capacity for DNA synthesis is increasing and costing less; new tools are being developed for fast, large-scale genetic manipulation; and more tested genetic parts are available for use, as is the knowledge of how to use them effectively. These advances promise to unlock an exciting array of 'smart' bacteria for clinical use but will also challenge scientists to better optimize preclinical testing regimes for early identification and validation of promising strains and strategies. Here, we review recent advances in the development and testing of engineered bacterial diagnostics and therapeutics. We highlight new technologies that will assist the development of more complex, robust and reliable engineered bacteria for future clinical applications, and we discuss approaches to more efficiently evaluate engineered strains throughout their preclinical development.